Sources of polychlorinated biphenyls to Upper Hudson River fish post-dredging. (January 2023) - Capozzi, Staci L.; Francisco, Kelly L.; Stahl, Briana L.; Al Hello, Mohson; Meixler, Marcia S.; Rodenburg, Lisa A.
Abstract: Polychlorinated biphenyls (PCBs) are persistent, bioaccumulative, and toxic chemicals that are the dominant contaminant in the Upper Hudson River (UHR) in New York State where two General Electric (GE) plants historically discharged PCBs to the river. Portions of the UHR were dredged from 2009 to 2015 to address PCB contamination. In 2017, the first post-dredging survey of yearling feeder fish and sediment PCB contamination was conducted to establish a baseline for the recovery of the river. Prior analysis of the sediment data from the 2017 survey indicated that ∼2% of the PCBs in the surface sediment were higher in molecular weight than the formulation used by GE and therefore arose from non-GE sources. In this work, the fish PCB data from the 2017 survey were analyzed using Positive Matrix Factorization (PMF). Empirical Bayesian Kriging (EBK) was used to estimate PCB concentrations in the sediment at the locations where fish were collected. The results suggest that PCBs that are the products of microbial dechlorination bioaccumulate in the fish and represent 7% of the PCB mass in the fish data set. Further, the results suggest that about 13% of the PCBs in the fish may have come from non-GE sources. This is higher than the percentage of non-GE PCBs in the sediment, but can be explained by the higher molecular weight of the non-GE mixture which causes it to bioaccumulate more effectively than GE PCBs. Concentrations of the non-GE PCBs averaged about 240 ppb wet weight (whole body) in yearling feeder fish. The remedial goals range from 50 to 400 ppb ww in fillet for fish including piscivorous species that are likely to have higher PCB concentrations than feeder fish. Graphical abstract: Image 1 Highlights: PCB congeners were measured in fish samples from the Upper Hudson River. Fish samples were collected after remedial dredging was complete in 2017. Analysis of congener patterns found five factors from GE and one from non-GE sources. Non-GE sources accounted for about 13% of PCB mass in the fish.